2017
DOI: 10.1007/s00484-017-1318-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal modeling of hand, foot, and mouth disease as a function of meteorological variations in Chongqing, China

Abstract: Hand, foot, and mouth disease (HFMD) is an enterovirus-induced infectious disease, mainly affecting children under 5 years old. Outbreaks of HFMD in recent years indicate the disease interacts with both the weather and season. This study aimed to investigate the seasonal association between HFMD and weather variation in Chongqing, China. Generalized additive models and distributed lag non-linear models based on a maximum lag of 14 days, with negative binomial distribution assumed to account for overdispersion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The frequency of HFMD emergences peak twice in a year in countries with a tropical climate; however, it can be observed throughout the year. It exhibits a single annual rise in summer or fall in countries located at higher latitudes (Blomqvist et al 2010;Huang et al 2015;Wang et al 2017). In Turkey, individual studies showed that the frequency of HFMD rises during summer (Topkarcı 2013; Uğraş et al 2014;Yorulmaz and Onat 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of HFMD emergences peak twice in a year in countries with a tropical climate; however, it can be observed throughout the year. It exhibits a single annual rise in summer or fall in countries located at higher latitudes (Blomqvist et al 2010;Huang et al 2015;Wang et al 2017). In Turkey, individual studies showed that the frequency of HFMD rises during summer (Topkarcı 2013; Uğraş et al 2014;Yorulmaz and Onat 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chongqing adopted multiple meteorological parameters to quantify the association of daily weather variation with HFMD incidence (9). Besides the meteorological parameters, studies from the Central South University also explored the relationship between HFMD and fine particulate matter less than 10 (PM 10 ) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that may result from a combination of pathological immune responses and direct viral effects, but no effective treatment is currently available and no biomarker that can be used as an early warning for critical HFMD. Chongqing (southwest of China) is a high incidence area of severe and critical HFMD [3], but also a high incidence of vitamin D (VitD) deficiency and insufficiency [4]. Studies have already suggested that the deficiency of (VitD) was found in some critical and severe disease [5], and in our clinical practice, we also found some critical HFMD children with a very low serum concentration of 25-hydroxyvitamin D [25(OH)D].…”
Section: Introductionmentioning
confidence: 99%